One-Shot Full-Range Quantification of Multi-Biomarkers With Different Abundance by a Tandem Giant Magnetoresistance Assay - Meng, Fanda; Zhang, Lei; Lian, Jie; Huo, Weisong; Shi, Xizeng; Gao, Yunhua (Frontiers in Chemistry, 2022)
In this study, we report a tandem giant magnetoresistance (GMR) assay realized one-shot quantification of multi-biomarkers of infection, C-reactive protein (CRP) with procalcitonin (PCT) and neutrophil gelatinase-associated lipocalin (NGAL), that all could cover their clinically relevant concentrations range under different principle. In the presence of co-determined, we determine these three biomarkers in undiluted human blood serum in a single test. The tandem principle, on which quantification of CRP, combines a sandwich assay and an indirect competitive assay, which allows for the discrimination of the concentration values resulting from the multivalued dose response curve (‘Hook’ effect), which characterizes the one step sandwich assay at high CRP concentrations. Whereas, the entire diagnostically dynamic range, in quantification of PCT and NGAL, was achieved by differential coating of two identical GMR sensors operated in tandem, and combining two standard curves. The sensor covers a linear detection range for CRP concentration from 0.003-350 μg/mL, the detection limit (s/n=3) is 1 ng/mL. For PCT, the linear detection range is from 0.02 ng/mL to 100 ng/mL, the LOD is 0.01 ng/mL(s/n=3). For NGAL, the linear detection range is from 0.5-1500 ng/mL, the LOD is 0.08 ng/mL(s/n=3). The salient features are its dynamic range and small sample volume requirement (50 μL), and the need for a short measurement time of 15 min. These figures of merit, in addition to the low detection limit at par with established assay instrumentation, render it a prospective candidate for practical use in point of care analysis.